A Cost Analyses of the Five Public Colleges in Alberta 1970-71. Resource Allocations. Master Planning Monograph 8 - Cornish, D. J.; Batty, J. F.; Alberta Colleges Commission ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
Educational planning, whether conducted on an institutional or systemwide basis, is synonymous with the future allocation of human and physical resources for the purpose of achieving a desired future state. In order that allocative decisions might be made on rational grounds, it is necessary to identify and assess the implications of current and alternative resource allocations. The findings reported in this monograph provide intra-institutionally comparable expenditure data for each of the 5 public colleges in Alberta, and by so doing, provide a quantitative analysis of current resource allocation. In addition, the study details the specific data elements required and the collection and analysis procedures to be followed in conducting an expenditure analysis on an annual basis. The findings reported in this study should prove useful to administrators, faculty, and students in each public college as information for reviewing resource allocations and for relating expenditures to output measures and indicators. The methodology used in conducting the analysis should prove useful to administrators throughout the system of postsecondary education in their efforts to make the best possible use of the human and physical resources that are allocated to the educational enterprise. (Author/HS)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cost Effectiveness; Educational Administration; Educational Finance; Educational Planning; Higher Education; International Education; Resource Allocation